Kesepakatan Perjanjian Jual Beli Melalui Mesin Jual Otomatis (Vending Machine) Ditinjau Dari Aspek Hukum Perjanjian - Ndaomanu, Diah Anggraeni; Wauran, Indirani (UI Scholars Hub, 2021)
In the making of an agreement, it always refers to 4 (four) terms of the validity of the agreement which is regulated in Article 1320 of the Indonesian Civil Code. There is an important element from 4 (four) legal requirements named the agreement between the two parties. The background of this thesis writing is the development of technology where there are developments in the trade sector, namely buying and selling through vending machines without involving the seller directly or real. This research writing aims to determine the form of sale and purchase agreements through vending machines in terms of the legal aspects of the agreement. The writing of this research uses normative research and a statutory approach as well as a conceptual approach, so that it can be concluded that the agreement in buying and selling through vending machines appears when the buyer puts money into the vending machine and the goods come out.